GREEN SCHOOL: Environmental performance and perception: A post occupancy evaluation of two Singapore schools - Saadon, N. (2013)
PLEA 2011 - Architecture and Sustainable Development, Conference Proceedings of the 27th International Conference on Passive and Low Energy Architecture